TRIM13 inhibits cell migration and invasion in clear-cell renal cell carcinoma. (2nd October 2020) - Li, Hualei; Qu, Lili; Zhou, Rui; Wu, You; Zhou, Shujun; Zhang, Yueping; Cheng, Bing; Ni, Jian; Huang, Hua; Hou, Jianquan
Abstract: TRIM13, a member of the TRIM family, is a RING domain containing E3 ubiquitin ligase which plays critical roles in diverse cellular processes including cell death, cancer and antiviral immunity. However, its expression and molecular mechanism on renal cell carcinoma (RCC) have not been characterized. This study explored the clinical significance and biological function of TRIM13 in human RCC. Western blot analyses and Immunohistochemical were performed in RCC tissues. The clinical relevance of TRIM13 in RCC was evaluated by immunohistochemical staining using tissue microarray. The role of TRIM13 in migration was studied in renal cell carcinoma cell lines of 786- O through knocking down TRIM13 with siRNA and over-expression of TRIM13. The regulation of TRIM13 on migration and invasion were determined by wound-healing and transwell assays. Western blot analyses showed that TRIM13 expression was dramatically decreased in RCC tissues compared with adjacent non-tumorous tissues. Up-regulation of TRIM13 in 786- O cells resulted in decreased NF-kB, MMP-9 and p-AKT levels and the capability for migration and invasion. In contrast, the ectopic expression of TRIM13 decreased the migration and invasion ability of 786-O cells. These findings indicate that TRIM13 decreases RCC metastasis and invasion may serve as a candidate RCC prognostic marker and a potential therapeutic target.